Exploring the Antimicrobial, Antioxidant, and Antiviral Potential of Eco-Friendly Synthesized Silver Nanoparticles Using Leaf Aqueous Extract of Portulaca oleracea L. - Mohammed Ali Abdel-Rahman; Khalid S. Alshallash; Ahmed M. Eid; Saad El-Din Hassan; Mutaz Salih; Mohammed F. Hamza; Amr Fouda (Pharmaceuticals, 2024)
Herein, the prospective applications of green fabricated silver nanoparticles (Ag-NPs) within the biomedical field were investigated. The leaf aqueous extract of Portulaca oleracea L., a safe, cheap, and green method, was used to fabricate Ag-NPs. The maximum plasmon resonance of synthesized NPs has appeared at 420 nm. The various biomolecules present in the plant extract to assemble spherical Ag-NPs with sizes of 5–40 nm were analyzed using Fourier transform infrared and transmission electron microscopy. The Ag was the major content of the formed Ag-NPs with an atomic percent of 54.95% and weight percent of 65.86%, as indicated by EDX. The crystallographic structure of synthesized NPs was confirmed by the diffraction of the X-ray. The dynamic light scattering exhibits the homogeneity and mono-dispersity nature with a polydispersity index of 0.37 in the colloidal fluid and a zeta potential value of –36 mV. The synthesized Ag-NPs exhibited promising antimicrobial efficacy toward various prokaryotic and eukaryotic pathogenic microorganisms with low MIC values of 12.5 µg mL−1 and 6.25 µg mL−1, respectively. Additionally, the P. oleracea-formed Ag-NPs showed optimistic antioxidant activity assessed by DPPH and H2O2 assay methods with the highest scavenging percentages of 88.5 ± 2.3% and 76.5 ± 1.7%, respectively, at a concentration of 200 µg mL−1. Finally, the biosynthesized Ag-NPs showed high antiviral properties toward the hepatitis A virus and Cox-B4 with inhibition percentages of 79.16 ± 0.5% and 73.59 ± 0.8%, respectively. Overall, additional research is essential to explore the Ag-NP-based aqueous extract of P. oleracea for human health. In the current investigation the use of synthesized Ag-NPs as antimicrobial, antioxidant, and antiviral agents to protect against pathogenic microbes, degenerative diseases caused by various oxidative stresses, and deadly viruses is recommended.